2012
DOI: 10.1371/journal.pone.0050462
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Chronic Noise Is Related to Elevated Fecal Corticosteroid Metabolites in Lekking Male Greater Sage-Grouse (Centrocercus urophasianus)

Abstract: There is increasing evidence that individuals in many species avoid areas exposed to chronic anthropogenic noise, but the impact of noise on those who remain in these habitats is unclear. One potential impact is chronic physiological stress, which can affect disease resistance, survival and reproductive success. Previous studies have found evidence of elevated stress-related hormones (glucocorticoids) in wildlife exposed to human activities, but the impacts of noise alone are difficult to separate from confoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 67 publications
2
103
0
1
Order By: Relevance
“…For example, noise might also increase physiological stress levels (ref. 30, but see ref. 31) that could cause additional declines in body condition.…”
Section: Significancementioning
confidence: 99%
“…For example, noise might also increase physiological stress levels (ref. 30, but see ref. 31) that could cause additional declines in body condition.…”
Section: Significancementioning
confidence: 99%
“…Such challenges include unpredictable changes to weather patterns, including periods of low or high rainfall, storms or significant or rapid changes in temperature (23,26) and other variables that could be considered to signal environmental quality to an individual have similar effects on the HPA axis, including food availability, predation risk, anthropogenic disturbance levels and pollutants (23,26,(33)(34)(35)(36)(37)(38)(39)(40). Each of these factors has been shown to have the ability to trigger a stress response; however the strength of this response is often related to the environmental context within the experiment or study (34,35,(41)(42)(43)(44)(45)(46). For example, chronic exposure to lead can cause alterations in the amount of corticosterone produced under an acute stress in white storks (Ciconia ciconia) (41), however few studies have found active effects of pollutants on baseline levels of glucocorticoids (35,41).…”
Section: Stress: What Is It and How Is It Regulated?mentioning
confidence: 99%
“…Direct effects of wind energy development can include collision mortalities, but indirect effects of behavioral avoidance or displacement have also been documented in animal populations , Sovacool 2009, Johnson and Stephens 2011, Blickley et al 2012a, 2012b, Winder et al 2014b; but see Hale et al 2014). Anthropogenic disturbance may also induce physiological stress responses among animals in landscapes with energy development, reducing body condition or survival (Lima 1986, Mainguy et al 2002, Blickley et al 2012a, 2012b.…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic disturbance may also induce physiological stress responses among animals in landscapes with energy development, reducing body condition or survival (Lima 1986, Mainguy et al 2002, Blickley et al 2012a, 2012b. Lesser Prairie-Chickens (Tympanuchus pallidicinctus) avoid nesting near vertical structures and crossing transmission lines and roads , Pruett et al 2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation